2021
DOI: 10.1111/jfd.13361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water temperature on the morbidity of Tetracapsuloides bryosalmonae (Myxozoa) to brown trout (Salmo trutta) under laboratory conditions

Abstract: Proliferative kidney disease (PKD) is a disease found in salmonid fish that is widespread in Europe and North America. The dependency of the clinical signs on the water temperature is extensively reported in rainbow trout, but detailed information on brown trout is lacking. In this study, juvenile brown trout were exposed to the spores of Tetracapsuloides bryosalmonae and then kept at different ambient water temperatures (16°C, 19°C and 22°C) for 10 weeks along with recording of morbidity throughout the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 59 publications
(87 reference statements)
1
15
0
Order By: Relevance
“…Several factors have been suggested to influence the risk of infection and spread of T . bryosalmonae in lakes and rivers, often linked with increased water temperatures (Hendrick et al., 1986; Okamura et al., 2011; Rubin et al., 2019; Tops et al., 2006, 2009; Waldner et al., 2021), manipulations of watercourses, fish stocking, increased water pollution, differences in susceptibility and immune responses to the parasite (Bailey et al., 2019; Grabner & El‐Matbouli, 2009; Kumar et al., 2013; Ros et al., 2021; Schmidt‐Posthaus et al., 2017). Outbreak of PKD is observed when the water temperature exceeds 12–15°C for more than 14 days (Bettge, Segner, et al., 2009; Bettge, Wahli, et al., 2009; Brown et al., 1991; Ferguson, 1981; Hedrick et al., 1993; Okamura et al., 2011; Wahli et al., 2002), and high morbidity and mortality of wild salmonids associated with PKD are mainly observed during summer and early autumn in the Northern Hemisphere (Mo & Jørgensen, 2017; Okamura et al., 2011; Sterud et al., 2007; Wahli et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been suggested to influence the risk of infection and spread of T . bryosalmonae in lakes and rivers, often linked with increased water temperatures (Hendrick et al., 1986; Okamura et al., 2011; Rubin et al., 2019; Tops et al., 2006, 2009; Waldner et al., 2021), manipulations of watercourses, fish stocking, increased water pollution, differences in susceptibility and immune responses to the parasite (Bailey et al., 2019; Grabner & El‐Matbouli, 2009; Kumar et al., 2013; Ros et al., 2021; Schmidt‐Posthaus et al., 2017). Outbreak of PKD is observed when the water temperature exceeds 12–15°C for more than 14 days (Bettge, Segner, et al., 2009; Bettge, Wahli, et al., 2009; Brown et al., 1991; Ferguson, 1981; Hedrick et al., 1993; Okamura et al., 2011; Wahli et al., 2002), and high morbidity and mortality of wild salmonids associated with PKD are mainly observed during summer and early autumn in the Northern Hemisphere (Mo & Jørgensen, 2017; Okamura et al., 2011; Sterud et al., 2007; Wahli et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The parasite proliferation triggers intense granulomatous cellular reaction, finally causing swelling in these organs [ 41 , 42 ]. After resolution of clinical symptoms in terms of normal organ structure restoration is confirmed in surviving brown trout [ 7 , 12 , 43 ] and rainbow trout [ 33 ]. In the present work, we did not observe clinical signs at 17 wpe, indicating that the fish had recovered and the damage to the affected organs reversed.…”
Section: Discussionmentioning
confidence: 99%
“…Such an acceleration might result in a mismatch in life history traits that have been locally adapted to a phenomena that is affected by climatic conditions, as found in reproductive mistiming to food availability in temperate zone songbirds (Visser et al, 2004). Therefore, with ambient temperatures playing a dominant role in PKD as is suggested from laboratory experiments (Waldner et al., 2021), then intervention by development of resistant strains and stocking methods might be the only option to render salmonid ecosystems climate resilient under current climate change prognoses (see Section 5.5).…”
Section: Management Options For Mitigating Pkd In Salmonidsmentioning
confidence: 99%
“…Research efforts showed that managing water temperatures was key to reduce the damage of the disease to the aquaculture industry (Clifton‐Hadley et al., 1986; Feist, 2004; Ghittino et al., 2003). Changes in temperature affect the host immune responses towards the parasite and thereby modulate disease outcomes (Bailey et al., 2018), like susceptibility to develop PKD (Debes et al., 2017; Waldner et al, 2021), resistance to the parasite, meaning fish do not get infected and develop PKD (Foott & Hedrick, 1987), or tolerance to the disease, meaning fish do not develop PKD when they get infected with the parasite (Strepparava et al., 2018). Temperature also has a direct effect on the parasites themselves by influencing its proliferation and development (Okamura et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation